Influence of the Location of a Decision Cue on the Dynamics of Pupillary Light Response - Pandey, Pragya; Ray, Supriya (Frontiers in Human Neuroscience, 2022)
The pupils of the eyes reflexively constrict in light and dilate in dark to optimize the retinal illumination. Non-visual cognitive factors like attention, arousal, decision making etc. also influence pupillary light response (PLR). During passive viewing, the eccentricity of the stimulus modulates the pupillary aperture size driven by spatially weighted corneal flux density (CFD), which is the product of luminance by area of the stimulus. Whether the scope of attention also influences PLR remains unclear. In this study, we contrasted the pupil dynamics between diffused and focused attentional conditions during decision-making, while the global CFD was maintained the same in two conditions. A population of twenty healthy humans participated in a pair of forced choice tasks. They distributed attention to the peripheral decision cue in one task, and concentrated at the center in the other to select the target from four alternatives for gaze orientation. The location of the cue did not influence participants’ reaction time. However, the magnitude of constriction was significantly less in the task that warranted attention to be deployed at the center than on the periphery. We observed similar pupil dynamics when participants either elicited or cancelled saccadic eye movement, which ruled out pre-saccadic obligatory attentional orientation contributing to PLR. We further addressed how the location of attentional deployment might have influenced PLR. We simulated a bio-mechanical model of PLR with visual stimulation of different strengths as inputs corresponding to two attentional conditions. In this homeomorphic model, the computational characteristic of each element was derived from the physiological and/ or mechanical properties of corresponding biological element. Simulation of the model successfully mimicked observed data. In contrary to common belief that the global ambient luminosity drives pupillary response, results of our study suggest that the effective corneal flux density (eCFD) determined by the luminance multiplied by the size of the stimulus at the location of deployed attention in the visual space is critical for the magnitude of pupillary constriction.